An Overview of Microalgae Lipid Extraction in a Biorefinery Framework. (March 2017) - Roux, Jean-Maxime; Lamotte, Hadrien; Achard, Jean-Luc
Abstract: The interest in algae based biofuels has increased over the past few years because of their high potential to reduce the dependence on fossil fuels. Many methods for converting microalgae to biofuel have been proposed in the past; however, an economical and energetically feasible process for algal fuel production has not yet emerged, leading to some disappointment. To get such a process, an integrated microalgal biorefinery approach to obtain a full valorization of each raw microalgae component seems necessary. Moreover, several steps of any microalgal biorefinery model, ranging from species selection, cultivation, harvesting &dewatering and lipids extraction need still improvements to lower the global cost of the process. This review focuses on this latter step. It is shown that the wet route, skipping the drying step preceding the extraction step, seems to be the only way to produce a viable microalgae based biorefinery industry. On the other hand, an efficient cell disruption method, based on scalability, energy consumption, ability to improve lipid accessibility as well as mass transfer must be selected and in this context two promising studies are presented.